Validation of the Portuguese version of the Langer Mindfulness Scale and its relations to quality of work life and work-related outcomes - Junça Silva, A.; Caetano, A. (TPM - Testing, Psychometrics, Methodology in Applied Psychology, 2021)
Mindfulness is an active mindset characterized by novel distinction-drawing and has been related to happiness and well-being. This study aims to validate the Portuguese version of the Langer Mindfulness scale (LMS14), to explore its psychometric and structural properties, and to analyze the role of mindfulness on the relation between work characteristics and performance. We conducted three studies; the first (N = 141) tested the scale’s factorial structure and its psychometric properties. In the second we used two samples (N = 330) and tested the factorial structure of the scale, its reliability and validity. In the third (N = 154) we analyzed the moderating role of mindfulness in the relationship between autonomy and feedback with performance. Results showed three factors — novelty seeking, novelty producing, and engagement — and convergent, discriminant, and criterion validity as the scale correlates with well-being, affect, creativity, and work engagement. Results demonstrated that mindfulness moderates the link between autonomy and feedback with performance.